Continuing professional development of lecturer’s research training model based on research product - Aan Komariah, Asep Suryana, Junihot M. Simanjuntak, Udin Syaefuddin Sa’ud, (Opción, 2019)
This research specifically talks about the continuity development in the university through training model based on research product and publication of scientific work that support the university quality enhancement via qualitative methods with Research and Development (R&D) model approaches. As a result, the ongoing training has not been done programmatically and has not been able to make lecturers learn independently. In conclusion, product based training model development IS done through these steps: (a) analysis; (b) planning; (c) development; (d) implementation; (e) evaluation.